2020
DOI: 10.1186/s13765-020-0491-8
|View full text |Cite
|
Sign up to set email alerts
|

A trienone analog of curcumin, 1,7-bis(3-hydroxyphenyl)-1,4,6-heptatrien-3-one, possesses ROS- and caspase-mediated apoptosis in human oral squamous cell carcinoma cells in vitro

Abstract: The leading causes of oral cancer treatment failure are cancer metastasis and chemotherapeutic resistance. Thus, developing novel anticancer agents that are effective against those aggressive cancer cells would be important for complementary or alternative treatments. The objective of this study was to investigate cytotoxicity and anticancer mechanisms of a synthetic trienone analog of curcumin, 1,7-bis(3-hydroxyphenyl)-1,4,6-heptatrien-3-one (trienone 11), against human oral squamous cell carcinoma (OSCC) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The leading causes of OSCC treatment failure include metastatic spread, recurrence and poor drug efficacy ( 10 ). Furthermore, previous studies have reported that OSCC treatment failure is associated with drug resistance, which is mainly attributed to chemotherapeutic drug transportation, metabolic reprogramming, redox status and DNA repair ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leading causes of OSCC treatment failure include metastatic spread, recurrence and poor drug efficacy ( 10 ). Furthermore, previous studies have reported that OSCC treatment failure is associated with drug resistance, which is mainly attributed to chemotherapeutic drug transportation, metabolic reprogramming, redox status and DNA repair ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increments in reactive oxygen species (ROS) may induce OSCC cell death, and a decreasing trend in ROS is observed in patients with advanced stage OSCC, suggesting that ROS may be an important potential antitumor target in OSCC therapeutic strategies. In recent years, a number of medicinal herbs and their active ingredients have been reported to induce ROS-mediated apoptosis in OSCC cells, including curcumin ( 10 ), β-lapachone ( 14 ) and erufosine ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 ). The majority of chemotherapy drugs induce apoptosis ( 31 , 32 ). The results revealed that the co-treatment with C5E and gemcitabine was markedly more effective compared with the individual treatments alone at inducing S phase cell cycle arrest and early apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the trienone analogs in this study should improve their stability and activity. Recently, the trienone analogs including T-BDMC have been reported as candidates for developing potent anticancer agents against human oral squamous cell carcinoma with less toxicity against Vero cells, a normal cell line, than their respective curcuminoid analogs 10 , 37 . However, there is no report about the pharmacokinetic activity and bioavailability of the trienone analogs.…”
Section: Discussionmentioning
confidence: 99%